Factors Influencing the Choice of the Mean of Promotional Advertizing - إدريس, الفاضل تيمان; عبد الرحمن, أروى عارف; شكرت الله, أمل بشير (Gezira Journal of Economic and Social Sciences, 2010)
The research aims to explore the impact of income on the type of advertisement and to detect the factors influencing the selection of promotional advertisement. The study followed the descriptive, analytical methods. Data were collected via questionnaire, and then statistical techniques were used for the analysis. The study concludes that there is no significant relationship between advertisement and consumer’s levels of income. It is also concluded that short and repeated advertisements increase the desire of the consumers to buy more. The study explains the results and suggests some recommenda-tions.